2021
DOI: 10.3390/bs11120179
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypy, Lifestyle Behaviors, and Health Indicators in a Young Adult Sample

Abstract: Problematic lifestyle behaviors and high rates of physical illness are well documented in people with schizophrenia, contributing to premature mortality. Yet, there is a notable absence of research examining general lifestyle and health issues in participants at risk for psychosis. This form of research may help identify concerns that exist during prodromal periods related to future outcomes. Accordingly, the current study examined lifestyle and health in a nonclinical sample of 530 young adults with varying l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Only one study to date has examined all four aspects of nutrition, physical exercise, and sleep as healthy behaviors in schizotypy, while one other study has examined exercise, nutrition, and schizotypy. In a survey study of US university students (N = 530), Dinzeo and Thayasivam [ 55 ] found that increased schizotypy symptoms were associated with poorer sleep quality across positive, negative, and disorganized domains. Specifically, the authors found that individuals scoring high on all three schizotypy domains reported significantly more severe somatic symptoms, poorer psychological health (e.g., reduced engagement with health behaviors), and more sleep difficulties compared to individuals self-reporting as being low across all schizotypy domains.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study to date has examined all four aspects of nutrition, physical exercise, and sleep as healthy behaviors in schizotypy, while one other study has examined exercise, nutrition, and schizotypy. In a survey study of US university students (N = 530), Dinzeo and Thayasivam [ 55 ] found that increased schizotypy symptoms were associated with poorer sleep quality across positive, negative, and disorganized domains. Specifically, the authors found that individuals scoring high on all three schizotypy domains reported significantly more severe somatic symptoms, poorer psychological health (e.g., reduced engagement with health behaviors), and more sleep difficulties compared to individuals self-reporting as being low across all schizotypy domains.…”
Section: Resultsmentioning
confidence: 99%
“…This same phenomenon of stronger networks may not hold for item-level networks of one very specific aspect of social functioning (i.e., empathy), where the hysteresis principle of network theory stating that symptoms exacerbate one another may be less applicable. Furthermore, though high schizotypy has been associated with other negative mental health outcomes [ 70 , 71 , 72 ], including in undergraduate populations [ 73 , 74 ], it is possible that the degree of difference in psychological health between the high and low schizotypy groups in this sample was not great enough to be reflected in the network structures as would have been predicted by the hysteresis principle [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample was split into two groups, high and low schizotypy traits, using predetermined cutoffs (Cohen, Callaway, Najolia, Larsen & Strauss, 2012 ; Dinzeo & Thayasivam, 2021 ) based on scores on the schizotypal personality questionnaire (SPQ, Raine, 1991 ). There were significant differences on the SPQ between low ( M low =41.44, SD low = 9.74) and high ( M high = 69.20, SD high = 10.84) schizotypy groups t (29) = −7.51, p < .001, Hedges’ g = 10.56.…”
Section: Methodsmentioning
confidence: 99%
“…Two groups were then generated using the SPQ-BR to create low and high schizotypy (STPY) groups. Groups were created by using predetermined cutoffs (Cohen et al, 2012 ; Dinzeo & Thayasivam, 2021 ) where scores falling 1.65 SD above the mean were considered high STPY, while scores falling below the mean were considered low STPY. Any scores that fell within the mid-range were collapsed and added to the high group as only two participants fell in this “intermediate range.” The final groups were n = 16 low STPY and n = 15 high STPY.…”
Section: Methodsmentioning
confidence: 99%